Effectiveness of antiviral treatment of patients with chronic hepatitis C GT 1b depending on the presence of comorbid chronic renal insufficiency - H. V. Venytska; O. V. Riabokon (Zaporozhye State Medical University, 2022)
Aim. The aim of the work was to analyze the effectiveness of antiviral therapy (3D mode) in patients with chronic hepatitis C (CHC) GT1 in clinical practice, depending on the presence of comorbid chronic renal insufficiency stage V, who receiving hemodialysis. Materials and methods. 101 patients with CHC GT1 who received antiviral therapy (AVT) according to the scheme OBV/PTV/r + DSV ± RBV (3D-mode) during 12 weeks were included in the study. All patients with CHC were divided into two groups depending on the presence of comorbid chronic renal insufficiency (CRI): 92 patients who did not have accompanying CRI and 9 patients with comorbid CRI stage V who received program hemodialysis. Results. The effectiveness of antiviral therapy in patients with CHC GT1 according to the OBV/PTV/r + DSV ± RBV scheme in clinical practice was high in terms of the achievement of 12 weeks sustained virologic response (SVR 12) SVR 12 (94.1 %). The frequency of achieving SVR 12 in CHC patients without concomitant CRI was 94.6 %, and with of comorbid CRI stage V (hemodialysis) - 88.9 % and had not statistically significant differences (P > 0.05). Treatment according to the 3D-mode was accompanied with stable normalization of ALT activity in 86.0 % of patients with CHC, and the frequency of it is achievement did not depend on the presence of comorbid CRI stage V (100.0 % vs. 85.2 % in patients without the specified concomitant pathology, P > 0.05). Conclusions. The effectiveness of antiviral therapy in patients with CHC GT1 according to the OBV/PTV/r + DSV ± RBV scheme in clinical practice is high in terms of the achievement of SVR 12 (94.1 %) and does not depend in the presence of comorbid CRI stage V in the patient (94.6 % vs. 88.9 %, P > 0.05). The severity of liver fibrosis does not affect the effectiveness of AVT in patients with CHC GT1 in the presence of comorbid CRI stage V and without this comorbid condition.